INITIAL ADJUSTMENT AND MENTAL ISOLATION ANALYSIS IN THE MOVIE “ANNA AND THE KING” - Safnidar Siahaan (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
This study will be focused on the parts of the cultural adjustment process of the main character’s experience in the movie “Anna and The King”. The cultural adjument process consists of some stages, those are: honeymoon period, culture shock, initial adjustment, mental isolation, and acceptance and integration, but in this research the writer only focuses on the initial adjustment and mental isolation stage. The objective of the study is to analyze how the main character’s experiences cultural adjustment process relating to the initial adjustment and mental isolation based on Levine and Adelman theory known as the stage of the “W” pattern of cultural adjustment process. The writer used the descriptive qualitative method to analyze the main character’s experience in the movie. Initial Adjustment is stage relating to some difficulties and problems in culture shock but it will be solved by the main character. Furthermore, Mental isolation is the newcomer’s feeling that lost of self confident because the resulf of anxiety, depresion and loneliness.